Relative Intensity Noise of Gain-Switched Dual-State Lasing for an Insein(113)B Quantum Dot Laser - Nuran Dogru; Erkan Cengiz; Hilal S. Duranoglu Tunc (Nanomaterials)
The RIN of an InAs/InP(113)B quantum-dot laser for direct- and cascade-relaxation models is investigated under the gain-switching condition via the application of an optical Gaussian pulse to an excited state. A new method is proposed to obtain RIN curves by eliminating the cross-correlation between noise sources. In this way, the noise sources are described independently and simulated with independent white Gaussian random variables. The results revealed that the RIN spectrum of both models was the same, apart from the fact that the cascade-relaxation model generated somewhat shorter pulses than the direct-relaxation model. Nevertheless, the direct-relaxation model had a lower RIN than that of the cascade-relaxation model. Excited- and ground-state carrier noises strongly affected the RIN spectrum, whereas the wetting-layer carrier noise had a negligible effect. In addition, the capture and escape times significantly affected the RIN spectrum. The output pulses had a long pulse width for both models due to the long pulse width of the ground-state photons. Nevertheless, applying an optical Gaussian pulse to an excited state reduced the RIN of both models and produced narrower gain-switched output pulses.